Competitiveness of Beef Cattle Farming in Indonesia: Domestic Resources Cost Approach - Ari Abdul Rouf; Arief Daryanto; Anna Fariyanti (Indonesian Center for Animal Research and Development, 2014)
Beef demand in Indonesian people is supplied from the domestic and import production, including Australia and New Zealand. Domestic Resources Cost (DRC) is one of the indicators in free trade that is defined as one of the competitiveness criteria. The competitiveness is determined by several factors, including resource, labor, technology and market demand. Based on the previous research results, it was obtained that: (1) The availability of abundant feed through the grazing system and crops livestock system can provide comparative advantage (DRC = 0.08-0.54); (2) The type of beef cattle kept had a good competitiveness (DRC = 0.08-0.94); (3) The labor’s wage can simultaneously create competitiveness (DRC<1); (4) The technological factor on farm level showed that the higher Average Daily Gain (ADG) will make the competitiveness increased; and (5) The number of cattle had a positive causality on the competitiveness with a coefficient of 0.510. The smallholder farmer with the average farming scale of three heads per farmer had a lower competitiveness (DRC = 0.08) compared to the cattle fattening company (DRC = 0.01-0.02). The existing research showed that the beef cattle farming in several places in Indonesia had good competitiveness (DRC<1), but in some areas, its value was close to one (less competitive). Therefore, in order to improve the competitiveness, the formulation and implementation of the farm subsector policy should be regarded as a system including upstream to downstream subsystems so it is expected that the coordination and synergy policy among stakeholder and economic actor will be better. Key words: Beef cattle, competitiveness, domestic resources cost